A scoping review key elements and effects of cardiovascular disease management programs based on community-based participatory research. - Juhyeon Yang; Bohyun Park (PLoS ONE)
Background This scoping review analyses the literature on community-based participatory research (CBPR)-based cardiovascular disease (CVD) management programmes, examining the key elements of their development and implementation and exploring their effectiveness. Methods This scoping review's methodology had six stages: 1) identifying the research question; 2) identifying relevant studies-search strategy; 3) study selection; 4) charting the data; 5) collating, summarising, and reporting the results; and 6) consultation exercise. The databases used were PubMed, Cochrane, and CINAHL, for the period from 4 March to 3 April 2022. We selected studies 1) published after 2000; 2) targeting community residents over 18 years old; and 3) proposed a CBPR-based CVD management programme, described its development, and evaluated its effects based on its application. Data were extracted independently by each of the two researchers, using a standardised form. Results Among the key aspects of such programmes were the many cases where community organisations led establishment of partnerships and cases where a decision-making committee was formed. Regarding application of the CBPR principles, community partners participated only in executing the research, not in analysing and interpreting research results. In addition, among the 21 studies selected were 6 randomised controlled trials, all of which showed a significant positive effect in experimental groups compared to control groups. Conclusion Improvement strategies are needed to allow implementation of CBPR principles in a CBPR-based CVD management programme. Moreover, further verification of programme evaluation research methods is needed. Scoping review registration This protocol has been registered to the OSF registries. 0000000204460911. Key Elements and Effects of Cardiovascular Disease Management Programs Based on Community-based Participatory Research: Protocol for a Scoping Review'. OSF, 4 Sept. 2020. Web.